ANALISIS PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI - -, Rahmisyari (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
This researc was aimed to analize and measure the leadership style on the officialâs work motivation of Local Legislative Assembly of Gorontalo City.Â  In relation to this research, the population was the whole number ofÂ  Local Legislative Assembly members of Gorontalo City, of which 75 respondents categorized as Civil Servants.Â  ConsideringÂ  the relatively small population, the overall was taken to be studied.Â  The result of the research showed that the leadership syles measured using otoritary dimensions, democracy, and laisez faire indicated at average level based on the descriptive-qualitative analysis.Â  Statistically, the leadership styles had positive and significant effects on the officialsâ work motivation.Â  The pattern of relationship indicated that the leadership styles strongly determine the work motivation of Local Legislative Assembly officials of Gorontalo City. Keywords: leadership styles and work motivation